The value of secondary neoadjuvant chemotherapy in platinum-sensitive recurrent ovarian cancer: a case-control study post GOG-0213 trial - Gu, Hongyuan (J Ovarian Res, 2020)
BACKGROUND: The prognostic value and optimal resection outcome related factors of the secondary cytoreduction surgery (SCR) in Platinum-sensitive recurrent ovarian cancer (PSOC) patients were still in doubt. The present retrospective study aims to determine the relationship between the objective response of secondary neo-adjuvant chemotherapy (SNAC) and the resection outcome of SCR. METHODS: Data were reviewed from 142 type II PSOCs who underwent SCR in Jiangsu Institute of Cancer Research between 1996 and 2016. Among them, 55 cases received preliminary Platinum based SNAC before SCR. Logistic regression analysis was used to explore optimal SCR related factors. Cox proportional hazards model and log-rank test were used to assess the associations between the survival durations and covariates. RESULTS: Optimal initial CRS (p = 0.02), disappearance of ascites after SNAC (p = 0.04) recurrent status (p = 0.02) and longer Platinum-free interval (p = 0.01) were the independent indicators of optimal SCR. Optimal SCR was associated with time to progression (TTP) but not overall survival (OS) (p = 0.04 and p = 0.41). The TTP and OS of PSOCs underwent SNAC were similar to those patients underwent SCR (p = 0.71, and p = 0.77, respectively) directly. CONCLUSIONS: SNAC might be another choice for PSOCs were not suitable for directly SCR. Optimal SCR had survival benefit in PSOCs whenever underwent SNAC or not.